Improving Students’ Scientific Writing Skills through Discovery Learning in Science Learning: A Systematic Review - Opik Prasetyo; Bowo Sugiharto; Harlita Harlita (Postgraduate, University of Mataram, 2025)
Scientific writing skills are essential for students to express ideas or thoughts in various media such as practicum reports. This skills can be trained through the implementation of learning models that can empower science process skills, namely discovery learning. This study aims to analyse various articles related to the implementation of discovery learning models in science learning to improve students' scientific writing skills. This research is a systematic review with the PRISMA method using the keywords